142 Amyand's Hernia: An Extensive Review of History, Aetiopathogenesis, Symptomatology, and Management – Should We Scan, Scope & Snip?. (28th February 2022) - Ballanamada Appaiah, N.N.; Probert, S.; Menon, N.J.; Alam, S.
Abstract: Background: Amyand's hernia, first described by Claudius Amyand in 1735, continues to remain a diagnostic & therapeutic challenge. By definition includes inguinal herniae that contain the vermiform appendix. Aim: This up-to-date review aims to define and classify Amyand's hernia and suggest appropriate management options in the current era. Aim to shed light on the value of pre-operative cross-sectional imaging and the use of laparoscopic surgery to provide a one stop solution. Method: Published English literature was reviewed (1735–2021), using PubMed and Embase, combining the MeSH terms "hernia", "inguinal", "appendix", "Amyand", "low dose CT" and "laparoscopic herniotomy". Most cited open access reviews, case series and case reports were chosen to provide a framework. A recent case is described with selected images (radiological, histology and intra operative). Results: Since the original publication, by Claudius Amyand in 1735, there exists a gulf on this condition in the available British medical literature. Nearly 100, 000 hernia repairs are performed in the UK annually. If Amyand's hernia account for 1% of these (according to the most stated estimate), there should be a thousand Amyand's herniae repaired annually in the UK alone. Unfortunately, the management options remain nonstandard. Conclusions: Computerized tomography (CT) allows for pre-operative diagnosis and should be considered more often, even in children. Laparoscopic appendicectomy combined with a laparoscopic herniotomy is a safe one stop solution, in experienced hands, for paediatric patients.